Forecast of factors affecting the fair value accounting in Vietnamese listed companies - VU, KIM ANH THI; BUI, NGOC THI (The journal of contemporary issues in business and government, 2021)
This study aims to assess the adoption of fair value accounting in Vietnam, and to forecast factors affecting the fair value (FV) application in Vietnamese listed companies. So, we used multivariate regression analysis to assess the impact of each factor on the application of fair value accounting in Vietnam, by implementing a survey of 203 accountants and directors of Vietnamese listed companies in the period from 2017 to 2019. The research results show that: for both small and medium sized enterprises and large enterprises, human resource factors have the strongest positive impact on FV application, followed by benefit factor. The factors of difficulties negatively affect this application. And, the active market factors have contradictory impacts between these two groups of enterprises. Our findings provide the significant perspectives of applying FV in Vietnamese companies, as well as different recommendations to Vietnamese policy makers in developing the legal accounting framework.